Evaluation of the Implementation of Government Accounting Standards Statement (PSAP) Number 07 concerning Fixed Asset Accounting at the Bogor Regency Population and Civil Registration Service (DISDUKCAPIL) - Siti Futri Adiningsih; Andy Lasmana; Yuppy Triwidatin (Formosa Journal of Applied Sciences, 2023)
This study aims to find out how the implementation of fixed asset accounting and its conformity with the Statement of Government Accounting Standards Number 07 concerning Fixed Asset Accounting at Disdukcapil Bogor Regency. The type of data used is qualitative data. Sources of data used are primary data and secondary data. Data collection was carried out by means of documentation and interviews. The data analysis method used is the descriptive analysis method. The results of this study indicate that the accounting treatment of fixed assets at the Bogor Regency Population and Civil Registry Office includes classification, recognition, measurement, initial valuation of fixed assets, subsequent measurement of initial recognition, namely Depreciation and revaluation of fixed assets, disclosure and disposal and disposal of fixed assets in accordance with PSAP Number 07, except that Depreciation of Fixed Assets is not fully in accordance. Depreciation of fixed assets is not fully in accordance with PSAP Number 07 because it does not depreciate other fixed assets.